Students’ attitudes towards using mother tongue in EFL classrooms: A survey study at Tien Lang High School, Hai Phong - Đinh, Thị Xuyến (ĐHNN, 2017)
This study is an attempt to investigate whether or not students at Tien Lang High School support the use of Vietnamese in EFL classrooms and then compare high achievers’ and low achievers’ attitudes. A questionnaire was administered to 91 11th grade students at Tien Lang High School, Hai Phong. Then, the responses of 24 high achievers (11th grade English final mark is above 8.0), and 29 low achievers (English final mark is below 5.5) were compared. Ten students with different attitudes were then further investigated through an interview. The results show that all participants supported both teacher’s and students’ use of L1. Also, there was almost no difference between two groups, except for some reasons of motivation, level of proficiency, and the occasion of checking their production with their peers. However, the study also indicates that for the best use of Vietnamese, it should be used reasonably in L2 classrooms so as to expose students to English communicative opportunities as much as possible